SISTEM INFORMASI PENGENALAN RAMBU LALU LINTAS PADA ANAK-ANAK (SIPERLU) BERBASIS WEB - Muhammad Nur Fadhilah; Nur Fadhilah, Muhammad; Rivaldi, Muhammad (Informatics and Computer Engineering Journal, 2022)
Traffic Signs are the main device in the traffic control system which basically functions to regulate and protect all traffic smooth, orderly, safe, and secure. until the goal of one of the alternative steps to minimize the incidence of accidents on the highway is with early childhood education related to traffic regulations. The author's goal is to create an Information System for the introduction of Web-Based Traffic Signs for Children in elementary school students to facilitate students in learning, by developing learning methods for children based on technology and information. to help children learn, especially in education and must be obeyed for the traffic sign, this Web-Based Information System for the introduction of Traffic Signs for Children In its development the author uses a method consisting of planning, analysis, design and implementation. Besides that, in collecting data, the authors made direct observations through interviews and literature studies in order to strengthen the data scientifically. The results of the analysis show that in order for learning to be more optimal, adjustments are needed to this increasingly rapid technological development. As one of the adjustment efforts is to provide learning through a programming medium.